A MICROSCOPIC STUDY ANALYSING THE EXTENSION OF A BURN LESION PRODUCED „IN VITRO” ON RADICULAR DENTIN USING THE DENTAL LASER - Elena Zabrac; Ioana Suciu; Bogdan Dimitriu; Mihai Ciocîrdel; Cristina Coralia Nistor; Ruxandra Bartok; Oana Amza (Romanian Journal of Oral Rehabilitation)
This “in vitro” study is intended to demonstrate the possible negative effects on dentin structure during decontamination of the endodontic system, assisted by the dental laser.